Effect of influent nutrient ratios and hydraulic retention time (HRT) on simultaneous phosphorus and nitrogen removal in a two-sludge sequencing batch reactor process - Wang, Yayi; Peng, Yongzhen; Stephenson, Tom (Elsevier Science B.V., Amsterdam., 2009)
A laboratory-scale anaerobic–anoxic/nitrification sequencing batch reactor (A2N- SBR) fed with domestic wastewater was operated to examine the effect of varying ratios of influent COD/P, COD/TN and TN/P on the nutrient removal. With the increased COD/P, the phosphorus removals exhibited an upward trend. The influent TN/P ratios had a positive linear correlation with the phosphorus removal efficiencies, mainly because nitrates act as electron acceptors for the phosphorus uptake in the A2N-SBR. Moreover, it was found that lower COD/TN ratio, e.g. 3.5, did not significantly weaken the phosphorus removal, though the nitrogen removal first decreased greatly. The optimal phosphorus and nitrogen removals of 94% and 91%, respectively were achieved with influent COD/P and COD/ TN ratios of 19.9 and 9.9, respectively. Additionally, a real-time control strategy for A2N-SBR can be undertaken based on some characteristic points of pH, redox potential (ORP) and dissolved oxygen (DO) profiles in order to obtain the optimum hydraulic retention time (HRT) and improve the operating reliabilit
Keywords: Sequencing batch reactor (SBR); Anaerobic-anoxic/nitrification (A2N); Denitrifying phosphorus removal organisms (DNPAOs); Nutrient ratios; Real-time control